Original Article Nootropic Medicinal Plants; Evaluating Potent Formulation By Novelestic High throughput Pharmacological Screening (HTPS) Method: Evaluating Potent Formulation By Novelestic HTPS Method - Shibnath Kamila,; N.V. Satheesh Madhav, (Iranian Journal of Pharmaceutical Sciences, 2017)
The principle of this method was to screen the pharmacological activity of six prepared polyphyto formulations by using high throughput screening method for their nootropic action. The study was performed in three stages using one, two and three animals, respectively in a group. Test formulations were given p.o daily at the dose of 50 and 100 mg/kg body weight. The test formulations were compared with the standard drug Bacopa monnieri for learning and memory enhancement. The pharmacological response shown in single experimental animal was compared with that shown in two animals by using regression analysis. R2 value was determined by Least squares linear regression analysis to interpret as the proportion of the variance in the dependent variable that is predictable from the independent variable. Of the six formulations, three were considered for further evaluation in three groups (n=3). Finally, one formulation that showed maximum response was tested in a group of 12 animals. One way ANOVA was used for estimating the statistical significance. The best formulations FM-06 (compose of Celastrus paniculatus, Habiscus rosasinensis, Bacopa monnieri, Convolvulus pluricaulis, Phyllanthus emblica, and Mentha piperita) was selected by high throughput screening and results for twelve animals in a group were found to be statistically similar.